Prevalence and Antifungal Susceptibility Profile of Oral Candida spp. Isolates from a Hospital in Slovakia - Lucia Černáková; Anna Líšková; Libuša Lengyelová; Célia F. Rodrigues (Medicina, 2022)
Oral fungal infections are a worldwide healthcare problem. Although Candida albicans is still the most common yeast involved in the infections of oral cavity, non-Candida albicans Candida species (NCACs) have been highly related to these infections, particularly in older, immunosuppressed or patients with long exposure to antimicrobial drugs. The goal of this work was to perform a quick epidemiological and mycological study on the oral samples collected from a laboratory of a hospital in Slovakia, for 60 days. The samples’ identification was performed by Germ-tube formation test, CHROMID® Candida, Auxacolor 2, ID 32C automated method, and the antifungal susceptibility testing determined by E-test®. Results confirm that comparing with bacteria, yeasts still occur in the lower number, but there is a high rate of antifungal resistance (81.6%)—to, at least one drug—among the collected samples, particularly to azoles and 5′-FC, which is clinically noteworthy.